Design of Teaching Materials Programming Basic C ++ Based on Sigil Software Learning Media - Rizky Amaliah; Sri Ilyen (Universitas Negeri Padang, 2021)
This study examined the creation of C ++ programming learning media using Sigil software. The reason for this research is as one of the conditions for ICT-based learning design courses. The purpose of this study is to produce an interactive learning media Electronic Publication (Epub) using SIGIL software. The media creation process is designed using the waterfall model software design method, including: design, architectural design and interface, coding / programming, and testing. The Sigil software-based learning media consists of a table of contents, subject matter, quizzes or exercises, quiz scores or exercises. The feasibility test on the results of the development and making process material for Programming Language C ++ Software Sigil is done using a Black-box testing testing. The results of these tests are the basic programming learning media C ++ based on Sigil software running well as the navigation-navigation function in each page, no error in the basic programming learning media C ++-based Sigil software has run according to the expected goal.